Structural characterization of three types of woods in Sudan: (Anogeissus leiocarpus) Sahab, (Balanites aegyptiaca) Heglieg, and (Sclerocarya birrea) Humeid. (September 2022) - Abdelatif, Amged O.; Abdrahman, Rihab A.; Abdalla, Ashraf M.A.
Abstract: Sudan has a great diversity of tree species and wood resources which are mainly used in furniture and tradition houses. However, the structural properties of these woods are not structurally classified which hinder use them by structural designers. Therefore, this paper aims to structurally classify some Sudanese timber species. Namely Sahab (Anogeissus leiocarpus), Heglieg (Balanites aegyptiaca), and Humeid (Seclerocarya birrea). Both physical properties and mechanical are tested using 540 test specimens from the three species and their characteristic strength was determined in accordance with BS EN 384 (2004). Based on the results, Sahab is structurally characterized as D27 hardwood, Heglieg is characterized as D45 hardwood, and Humeid is characterized as C14 softwood as per BS EN 338:2004 strength classes.